D. Clint Burnett, Paul and Imperial Divine Honors: Christ, Caesar, and the Gospel (Grand Rapids, MI: Eerdmans 2024) - Marcin Kowalski (The Biblical Annals)
Book review: D. Clint Burnett, Paul and Imperial Divine Honors: Christ, Caesar, and the Gospel (Grand Rapids, MI: Eerdmans 2024). Pp. 316 + xxvi. 49,99 USD (hardcover/ebook). ISBN 978-0-8028-7985-1.